Sistem Pengendalian Manajemen sebagai Kunci Peningkatan Kinerja pada Perusahaan Penyedia Layanan Internet PT. Benknet - L. Jatmiko Jati; M. Najmul Fadli; Helna Wardhana; Irwan Cahyadi (Target : Jurnal Manajemen Bisnis, 2023)
PT. Benknet is a company that focuses on providing internet services in the village of O'o, Dompu District, Dompu Regency. As of 2018 until now, PT. Benknet controls several areas to provide internet services, including the areas of Dompu District, Hu'u District, Pajo District, Pekat District to include the Bima Regency area to be precise in Woha District, Sila Village and its surroundings. The phenomenon that occurs in this study is the success of PT. Benknet to aggressively expand its services so as to be able to provide internet services in a wide area for 6 years. The qualitative approach is the approach used in this study which is intended to describe reality or know from events that are used as research objects which then make it easier to obtain objective data. The results of this study indicate the management of PT. Benknet performs structured management control in both formal control systems and informal control systems so that all management functions run effectively and efficiently. PT management Benknet is fully aware of the importance of implementing a Management Control System in the company to ensure the company's performance is in accordance with management's plans and expectations. In addition, it turns out that the management of PT. Benknet understands how to apply a good and correct Management Control System so that PT. Benknet was able to achieve success and still survive as one of the largest internet service providers for 6 years.